GEMPUR STUNTING DENGAN “NAGITA” DI KELURAHAN BALELA KECAMATAN LARANTUKA - Mudmainna Mudmainna; Brigita Elisabet KR. Uran; Reinaldis Masi (LPPM Institut Pendidikan Nusantara Global, 2025)
The training activity with the theme “Combating Stunting with Nagita (Tuna Nuggets) in Balela Village” was successfully conducted overall. The local PKK women’s group demonstrated great enthusiasm in learning food processing techniques, particularly in creatively transforming tuna fish into nutritious side dishes and snacks. This initiative is highly relevant given that tuna is both rich in nutrients and abundantly available in Balela Village, East Flores Regency. The program began with a presentation by the team on the nutritional content of tuna, followed by a hands-on session where participants practiced processing tuna into nuggets. The activity received positive responses from both participants and village officials, as reflected in the readiness of facilities and infrastructure, as well as the participants’ active involvement throughout all stages of the training. All participants remained engaged until the end of the program, with none leaving the venue prematurely. The outcome of the training, in the form of Tuna Nugget products, was directly consumed together at the activity site, providing not only a pleasant learning experience but also tangible benefits for the community.